Design of dual‐outputs‐single‐stage a‐Si:H TFT gate driver for high resolution TFT‐LCD application. Issue 5 (4th May 2016) - Zheng, Guang‐Ting; Liu, Po‐Tsun; Wu, Meng‐Chyi
Abstract: A new gate driver has been designed and fabricated by amorphous silicon technology. With utilizing the concept of sharing the noise free block in a single stage for gate driver, dual‐outputs signals could be generated in sequence. By increasing the number of output circuit block in proposed gate driver, number of outputs per stage could also be adding that improves the efficiency for area reduction. Besides, using single driving thin‐film‐transistor (TFT) for charging and discharging, the area of circuit is also decreased by diminishing the size of pulling down TFT. Moreover, the proposed gate driver has been successfully demonstrated in a 5.5‐inch Full HD (1080xRGBx1920) TFT‐liquid‐crystal display panel and passed reliability tests of the supporting foundry. Abstract : A new gate driver has been designed and fabricated by amorphous silicon technology. With utilizing the concept of sharing the noise free block in a single stage for gate driver, dual‐outputs signals could be generated in sequence and the proposed gate driver has been successfully demonstrated in a 5.5‐inch Full HD (1080xRGBx1920) TFT‐Q4 liquid‐crystal display panel and passed reliability tests of the supporting foundry.